My textbook says to do the following steps to simplify the $\sqrt{3/2}$:

$\sqrt{3/2}=\sqrt{((3/2)\times (2/2))} =\sqrt{6/4} = \sqrt{6}/\sqrt{4}=\sqrt{6}/2.$

However, if the fourth step is valid (1. please explain why and 2. I specifically mean where you "split" the square root into two parts), then why can't you simply do:


Why wouldn't that be valid?

My point is, are the two fractions equivalent?


It is true that $\sqrt{3/2} $ is equal to $\sqrt{3}/\sqrt{2}$.

However, the point of the transformations you give it to have a denominator without root.

More generally, for positive $a,b$ it is always true that $\sqrt{ab} = \sqrt{a}\sqrt{b}$ and $\sqrt{a/b}=\sqrt{a}/ \sqrt{b}$.

To see that note $(\sqrt{a}\sqrt{b})^2 =(\sqrt{a})^2(\sqrt{b})^2 =ab$, thus $\sqrt{a}\sqrt{b}$ is the square-root of $ab$, that is it is $\sqrt{ab}$. And likewise for the second.

  • $\begingroup$ Thanks for editing the Mathjax for me! I couldn't find a help website where I could look up how to use it. Could you provide a link for me please? $\endgroup$ – user49558 Aug 12 '16 at 19:02
  • $\begingroup$ and moreover are you saying that the sqrt(3)/sqrt(2)=sqrt(6)/2? $\endgroup$ – user49558 Aug 12 '16 at 19:05
  • $\begingroup$ You are welcome. You had it almost right, mainly it was just that you need backslashes before sqrt. See meta.math.stackexchange.com/questions/5020/… for an intro. On the math, yes the two are equal. Square both sides to get $3/2$ and $6/4$ respectively, which is the same. $\endgroup$ – quid Aug 12 '16 at 19:10
  • $\begingroup$ 2. Also, this is kind of unrelated, but I can't find a way to log out of Stackexchange completely. Do you know a way? $\endgroup$ – user49558 Aug 12 '16 at 19:14
  • $\begingroup$ @user49558 Please kindly look it up here and here. $\endgroup$ – dbanet Aug 12 '16 at 19:19

It is true that $$\sqrt{\frac32} = \frac{\sqrt{3}}{\sqrt{2}}. $$

Generally, when one simplifies fractions involving square roots, you want to remove all square roots in the demoninator so

$$\sqrt{\frac32} = \frac{\sqrt{3}}{\sqrt{2}} = \frac{\sqrt{3}}{\sqrt{2}}\cdot\frac{\sqrt{2}}{\sqrt{2}} = \frac{\sqrt{3}\sqrt{2}}{2} $$

You also have that $$\frac{\sqrt{6}}{2} = \frac{\sqrt{3\cdot 2}}{2} = \frac{\sqrt{3}\sqrt{2}}{2}, $$ so you can write the same things in different ways: $$\sqrt{\frac32} = \frac{\sqrt{3}}{\sqrt{2}} = \frac{\sqrt{6}}{2} = \frac{\sqrt{3}\sqrt{2}}{2}. $$ It just depends on what is considered "most simplified."

  • $$\frac{\sqrt{3}}{2}=\frac{\sqrt{3}}{\sqrt{2^2}}=\frac{\sqrt{3}}{\sqrt{4}}=\sqrt{\frac{3}{4}}$$
  • $$\sqrt{\frac{3}{2}}=\sqrt{\frac{2\cdot3}{2\cdot2}}=\sqrt{\frac{6}{4}}=\frac{\sqrt{6}}{\sqrt{4}}=\frac{\sqrt{6}}{\sqrt{2^2}}=\frac{\sqrt{6}}{2}$$

And if I read it right:



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.